Rebranding and Digital Marketing of “Lejareh” Beverage at Ranting 'Aisyiyah Sidodadi - Damayanti, Adinda Putri; Putri, Pingkan Novita Yanda; Santoso, Rachmat Adi; Abidin, Zainul; Maryam, Effy Wardati (Universitas Muhammadiyah Sidoarjo, 2025)
This community service aims to increase the competitiveness and sustainability of the Lejareh ‘Aisyiyah Beverage UMKM in Ranting ‘Aisyiyah Sidodadi, Candi, Sidoarjo through a product rebranding strategy. Lejareh drinks, which are local products based on natural ingredients, have great potential for further development to meet increasingly competitive market needs. Service activities include packaging improvements, upgrading packaging labels, as well as operating offline and digital marketing. The results of the activity showed a significant increase in brand image and market acceptance of the newly packaged product. Apart from that, knowledge of UMKM players regarding marketing strategies and business management has also increased. It is hoped that this positive impact can encourage local economic growth and strengthen the economic independence of the ‘Aisyiyah community in the Sidodadi area.